PEMETAAN SEBARAN BATUAN PENYUSUN PAGAR CANDI DI SITUS CANDI LOSARI DUSUN LOSARI, DESA SALAM, KECAMATAN SALAM, KABUPATEN MAGELANG BERDASARKAN METODE MAGNETIK - Novi Dwi Ariani; Thaqibul Fikri Niyartama; Nugroho Budi Wibowo (Balai Arkeologi Yogyakarta, 2013)
Mapping geophysics research was conducted by geomagnetic method to know anomaly pattern of magnetic pole and to know distribution location and depth of temple gate composing stone in Losari Temple Site by using magnetic data. Data collection used Proton Precessions Magnetometer (PPM) G-856AX by area width of 88 km x 40 km and measurement space of 3 meter used looping method. Field data was corrected by daily variation and IGRF (International Geomagnetics Reference Field) correction and then reduction to pole. The slice modeling was conducted on local anomaly map on height of 6 meter. The result of the local magnetic field anomalies incision then interpolated to get an idea of the spread and depth of rocks making up the fence Losari temple. Local anomaly map shows that anomaly position lies in southwest, southeast, and northeast from main temple. Based from interpolated distribution of magnetic pole anomaly is dominated in depth of 2 meter to 4 meter.